Advance Method for Security Enhancement in Optical Code Division Multiple Access System. Issue 1 (2nd January 2018) - Gupta, Sumit; Goel, Aditya
Abstract: This paper proposes a new design of encoder and decoder with novel code design for one–dimensional (1D) (spectral domain) and two-dimensional (2D) (spectral and time domain) optical code divisions multiple access system. The suggested code has a zero cross-correlation property in 1D and 2D modes, so multiple-access interference (MAI) is totally eliminated. In proposed new encoder, code reconfiguration is achieved within two users in each group at the transmitter end with defined sequence. This approach degrades the code detection probability at the receiving end against the eavesdropper in the presence of single user in network. Another switching improves the code security against the on–off energy-level detection at the transmitter end. The mathematical and simulation analysis is performed for the proposed code. The probabilities of code estimation at the transmitter and receiver ends are analysed which shows a better confidentiality. The mathematical analysis shows that the proposed code has a better performance than the existing 1D random diagonal, 1D modified double-weight, 2D perfect difference, and 2D diluted perfect difference codes.